Importance of snow to global precipitation. Issue 21 (11th November 2015) - Field, P. R.; Heymsfield, A. J.
Abstract: Precipitation controls the availability of drinking water and viability of the land to support agriculture. Failure to accurately predict the location, magnitude, and frequency of precipitation impacts not only numerical weather forecasting but also climate modeling. It has been proposed that most rainfall events originate from ice that has melted to form rain. Here we use remote sensing from spaceborne cloud radar to quantify that idea. A new metric is constructed to quantify the fraction of rain events at the surface that are linked to snow melting at a higher altitude. CloudSat is used to show the global variation of the importance of snow in the precipitation process. In the tropics, subtropics, midlatitude and polar regions 0.3, 0.4, 0.8, and >0.9, respectively, of all precipitation events (>1 mm/d) are linked to the production of snow in clouds. Key Points: Globally, half of precipitation events are snow or come from melting snow Thirty percent of the precipitation events in the tropics come from melting snow This metric can be used to test other models